2022
DOI: 10.1038/s41588-022-01204-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding variants disrupting a tissue-specific regulatory element in HK1 cause congenital hyperinsulinism

Abstract: Introductory paragraph Gene expression is tightly regulated with many genes exhibiting cell-specific silencing when their protein product would disrupt normal cellular function 1 . This silencing is largely controlled by non-coding elements and their disruption might cause human disease 2 . We performed gene-agnostic screening of the non-coding regions to discover new molecular causes of congenital hyperinsulinism. This identified 14 non-coding … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 50 publications
0
14
1
Order By: Relevance
“…These features are similar to promoter element features of housekeeping genes, tailored for their ubiquitous expression [67]. HK1 promoter also contains regulatory sites known as sp sites within the P2 BOX which are essential for promoter activity and binding of protein factors in lower vertebrates to humans [60,68,69]. The role of non-coding elements in regulating HK1 and their association with congenital hyperinsulinism has also been reported [68].…”
Section: Regulation Of Hexokinase Expressionmentioning
confidence: 82%
See 1 more Smart Citation
“…These features are similar to promoter element features of housekeeping genes, tailored for their ubiquitous expression [67]. HK1 promoter also contains regulatory sites known as sp sites within the P2 BOX which are essential for promoter activity and binding of protein factors in lower vertebrates to humans [60,68,69]. The role of non-coding elements in regulating HK1 and their association with congenital hyperinsulinism has also been reported [68].…”
Section: Regulation Of Hexokinase Expressionmentioning
confidence: 82%
“…HK1 promoter also contains regulatory sites known as sp sites within the P2 BOX which are essential for promoter activity and binding of protein factors in lower vertebrates to humans [60,68,69]. The role of non-coding elements in regulating HK1 and their association with congenital hyperinsulinism has also been reported [68]. Alternative splicing forms multiple HK1 isoforms, i.e., HK1 (ubiquitous), HKR (erythrocytes), HK-TA/TB (testis-A/B), HK-TB (testis-B), and HK-TD (testis-D).…”
Section: Regulation Of Hexokinase Expressionmentioning
confidence: 99%
“…These features are similar to promoter element features of housekeeping genes, tailored for their ubiquitous expression [64]. HK1 promoter also contains regulatory sites known as sp sites within the P2 BOX, which are essential for promoter activity and the binding of protein factors in lower vertebrates to humans [57,65,66]. The role of non-coding elements in regulating HK1 and their association with congenital hyperinsulinism has also been reported [65].…”
Section: Regulation Of Hexokinase Expressionmentioning
confidence: 82%
“…HK1 promoter also contains regulatory sites known as sp sites within the P2 BOX, which are essential for promoter activity and the binding of protein factors in lower vertebrates to humans [57,65,66]. The role of non-coding elements in regulating HK1 and their association with congenital hyperinsulinism has also been reported [65]. Alternative splicing generates multiple HK1 isoforms, i.e., HK1 (ubiquitous), HKR (erythrocytes), HK-TA/TB (testis-A/B), HK-TB (testis-B), and HK-TD (testis-D).…”
Section: Regulation Of Hexokinase Expressionmentioning
confidence: 99%
“…2). Recently, Wakeling et al performed whole genome sequencing on 135 individuals with genetic testing negative HI and identified non-coding variants within a regulatory region of HK1 intron 2 that co-segregated with disease in families [7 ▪▪ ]. Using epigenomic analysis, single-nuclei assay for transposase-accessible chromatine with sequencing and a high-throughput genomic and epigenomic technique, they demonstrated that these variants encompass a region of chromatin accessibility within a regulatory domain for the HK1 promoter.…”
Section: Molecular Mechanisms Of Diseasementioning
confidence: 99%